Contributions towards the hazard evaluation of two widely used cytostatic drugs - Monteiro, Bruna (2022)
Cytostatic drugs are one of the most important therapeutic options for cancer, a disease that is expected to affect 29 million individuals by 2040. After being excreted, cytostatics reach wastewater treatment plants (WWTPs), which are unable to efficiently remove them, and consequently, they will be released into the aquatic environment. Due to the highly toxic properties of cytostatics, it is particularly relevant to evaluate their potential ecological risk. Yet, cytostatics toxicity data is still not available for various species. In this work, the ecotoxicity of two widely consumed cytostatics, cyclophosphamide (CYP—as a model cytostatic) and mycophenolic acid (MPA—as a priority cytostatic), was evaluated on three freshwater species—Raphidocelis subcapitata, Brachionus calyciflorus, and Danio rerio, and the risk quotient (RQ) was assessed. Both drugs significantly affected the yield and growth inhibition of the microalgae, while for rotifers, the least sensitive species, only significant effects were registered for CYP. These drugs also caused significant effects on the mortality and morphological abnormalities on zebrafish. The estimation of the RQ discloses that CYP seems to pose a low risk to aquatic biota while MPA poses a very high risk. Altogether, these results emphasize the need for more complete environmental risk assessments, to properly prioritize and rank cytostatics according to their potentially toxic effects on the environment and aquatic biota.